AI-ENGAGE: A Multicentre Intervention to Support Teaching and Learning Engagement with Generative Artificial Intelligence Tools - Keelin Leahy; Ekin Ozer; Eoin P. Cummins (Education Sciences)
The emergence of generative artificial intelligence (GenAI) chatbots, such as ChatGPT, presents unique challenges and opportunities in an educational setting; however, they lack empirical evidence as teaching and learning tools. This study sought to investigate the impact of teacher-led AI-focused interventions in higher education institutions in different subject areas. Our aims were to support student engagement, explore the impact of AI tools for learning engagement and efficiency and skill development, and promote awareness of the strengths and limitations of GenAI tools in an educational context. This study was carried out with three distinct cohorts; Physiology, Initial Teacher Education, and Engineering, with year 3 and 4 undergraduate students. Each cohort received two 50 min teacher-led AI-focused interventions, including practical exercises relevant to the specific discipline. Following the interventions, students from all three cohorts received a common (optional) survey that quantitatively and qualitatively evaluated their experiences. Data from the three cohorts was pooled for analysis, with individual cohort analyses for Physiology, Initial Teacher Education, and Engineering provided. Our data indicates that teacher-led introductions to AI tools have positive effects on student engagement with peers, educators, and most notably the subject the students engage in. Students also reported very positive supportive effects with respect to learning engagement, learning efficiency, and critical thinking skills. Students found GenAI tools most useful for gathering knowledge and research purposes, while notable limitations included challenges associated with generating prompts and the accuracy of information. Students noted plagiarism as a significant ethical concern. Taken together, our data collected from diverse teaching and learning contexts support the use of teacher-led AI-focused interventions, specifically ChatGPT, in third-level education. Approaches like this are highly relevant to the university teaching of Physiology, Initial Teacher Education, and Engineering but are also more broadly applicable to third-level education in general to inform opportunities, limitations, and ethical considerations of GenAI in education.